Evaluation of the changes in serum iron levels in pre-eclampsia - Gupta, Shalini (Springer India, 1997)
Serum iron levels were studied in 50 patients with pre-eclampsia and the results were compared with 50 control cases. Their serum iron levels were found to be higher than the controls. Increase in serum iron was directly proportional to the increased levels of uric acid, urea and creatinine. Mean reticulocyte counts, plasma free haemoglobin and unconjugated bilirubin levels were also higher in these patients. It is suggested that haemolysis may be a major contributory factor for the increased levels of serum iron in pre-eclampsia.